Joint Subcarrier Assignment and Global Energy-Efficient Power Allocation for Energy-Harvesting Two-Tier Downlink NOMA Hetnets - Baidas, Mohammed W.; Al-Mubarak, Mubarak; Alsusa, Emad; Awad, Mohamad Khattar (IEEE access, 2019)
In this paper, the problem of joint subcarrier assignment and global energy-efficient power allocation (J-SA-GEE-PA) for energy-harvesting (EH) two-tier downlink non-orthogonal multiple-access (NOMA) heterogeneous networks (HetNets) is considered. Particularly, the HetNet consists of a macro base-station (MBS) and a number of small base-stations (SBSs), which are solely powered via renewable-energy sources. The aim is to solve the J-SA-GEE-PA maximization problem subject to quality-of-service (QoS) per user as well as other practical constraints. However, the formulated J-SA-GEE-PA problem happens to be non-convex and NP-hard, and thus is computationally-prohibitive. In turn, problem J-SA-GEE-PA is split into two sub-problems: (1) subcarrier assignment via many-to-many matching, and (2) GEE-maximizing power allocation. In the first sub-problem, the subcarriers are assigned to users via the Gale-Shapley deferred acceptance mechanism. As for the second sub-problem, the GEE-PA problem is solved optimally via a low-complexity algorithm. After that, a two-stage solution procedure is devised to efficiently solve the J-SA-GEE-PA problem, while ensuring stability. Simulation results are presented to validate the proposed solution procedure, where it is shown to efficiently yield comparable network global energy-efficiency to the J-SA-GEE-PA scheme, and superior to that of OFDMA; however, with lower computational-complexity. The algorithmic designs presented in this work constitute a step towards filling the gap for computationally-efficient and effective resource allocation solutions to guarantee a fully autonomous and grid-independent operation of EH two-tier downlink NOMA HetNets.